Unveiling Environmental Corrosion Mechanisms in Ancient Egyptian Bronze Spearheads for Conservation - El-Shamy, Ashraf M.; Megahed, Mohamed M.; El-Ashery, Noha H.; Saleh, Saleh M. (Journal of Environmental Accounting and Management, 2026)
This research examines twelve bronze spearheads from the Salah El-Din Military Museum in Cairo, Egypt, exhibiting significant corrosion. The study’s objective is to analyze the corrosion, identify resultant compounds, and determine the metals constituting these artifacts. This analysis aims to understand the corrosive factors and degradation mechanisms and inform scientifically based conservation treatments. Metallographic Microscope (ME), Scanning Electron Microscope & energy dispersive analysis (SEM&EDS), and X-ray diffraction (XRD) were used for examination. The artifacts were found to be primarily composed of bronze (copper and tin) with impurities such as iron and sulfur. Corrosion products identified included Cuprite, Brochantite, Paratacamite, Antlerite, and Quartz. Based on these findings, a chemical cleaning approach was deemed optimal, followed by the application of an advanced acrylic coating with Nanocomposite material to preserve and protect the spearheads from future deterioration.